The Founding Father of Korean Democracy beyond the Ideological Controversy: Tosan's Political Philosophy of the Humane Democracy and Its Moral Foundation (KEMANUSIAAN The Asian Journal of Humanities, 2012)
Although Tosan An Ch'ang-ho (Ahn, Chang-Ho: 1878–1938) is regarded as one of the key national leaders of Korea's independence movement in the early twentieth century, recent scholarship has discovered that An Ch'ang-ho is "an elusive figure in modern Korean history". The debate surrounding the identity of An Ch'ang-ho as a person and as a leader in Korea's independence movement is divided among scholars according to how he is understood with regard to his involvement in the independence movement. In this paper, I argue that the controversy is largely due to the interpreters' reductionist standpoint, which fails to integrate Tosan's foundational work in moral thought with his innovative insight in political philosophy. Later in this paper, through the critical and constructive integration of Tosan's moral and political ideas, I present the concept of "humane democracy" as Tosan's original contribution to the establishment of the Korean political philosophy of democracy.